Making Simple Repairs: Repairing Drawers - Mary N. Harrison (EDIS)
This document contains instructions on how to fix sticking drawers and loose or broken handles and nobs. This document is FCS5234-08, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.